Exposure to multiple metals and prevalence for preeclampsia in Taiyuan, China. (December 2020) - Wang, Ying; Wang, Keke; Han, Tianbi; Zhang, Ping; Chen, Xi; Wu, Weiwei; Feng, Yongliang; Yang, Hailan; Li, Mei; Xie, Bingjie; Guo, Pengge; Warren, Joshua L.; et al.
Highlights: Exposure to higher levels of multiple metals was associated with preeclampsia. The observed association is driven by a Cr, As, Hg and Pb metal mixture. Pre-pregnancy BMI may modify the association between Cr and preeclampsia. Abstract: Background: Several studies with small sample size have reported inconsistent associations between single metal and preeclampsia (PE). Very few studies have investigated metal mixtures and PE. Methods: Blood concentrations of chromium (Cr), cadmium, mercury (Hg), arsenic (As), lead (Pb), nickel, cobalt, and antimony were measured using inductively coupled plasma-mass spectrometry among 427 PE women and 427 matched controls from Taiyuan, China. Multivariate logistic regression models, weighted quantile sum (WQS) regression, and principal component analysis were employed to examine exposure to single metals and metal mixtures in relation to PE. Results: An increased prevalence of PE was associated with Cr (OR = 1.76, 95% CI: 1.18, 2.62 and 1.90, 1.22, 2.93 for the middle and high vs. low), Hg (OR = 1.60, 95% CI: 1.08, 2.38 for the high vs. low) and As (OR = 1.64, 95% CI: 1.07, 2.52 for the middle vs. low). The WQS index, predominated by Cr, Hg, Pb, and As, was positively associated with PE. A principal component characterized by Cr and As also exhibited excessive association with PE. The highest PE prevalence was found among women who were overweight/obese before pregnancy and had high Cr levels compared to women who had pre-pregnancy normal body mass index (BMI) and low Cr levels. Conclusions: Our study provided evidence that exposure to multiple metals was associated with increased prevalence of PE, and the observed association with multiple metals was dominated by Cr, As. Our study also suggested that pre-pregnancy BMI might modify the association between Cr and PE.